Impact of Energy-Efficient Electricity Usage Counseling on Community Behavior in Cibenda Village Pangandaran Regency - Ardiansyah, Neris Peri; Mayang K S, Ajeng; Barnadi, Yudi; Suryana, Ase (Institut Teknologi Nasional, Bandung, 2024)
In Indonesia, the household sector is one of the largest consumers of electricity, so it is necessary to optimize energy use to reduce costs and environmental impacts. This study aims to provide counseling on energy-efficient electricity usage techniques. Methods Activities carried out include lectures, discussions, demonstrations, and simulations. Counseling focused on the selection of efficient electrical equipment, the application of environmentally friendly technology, and strategies for effective and efficient electricity use. The results of the study showed that the counseling program on environmentally friendly technology and energy saving was well received by various community groups. Most respondents, including Karang Taruna youth 90%, village government officials 95%, PKK mothers 85%, and fishing communities 88%, considered this counseling useful. In addition, the majority felt more confident in choosing energy-efficient equipment 83-90% and understood more environmentally friendly technology 75-85%. Most also planned to implement 80-90% and had started implementing more energy saving techniques 70-80%. These results confirm the positive impact of counseling in increasing awareness and energy saving practices in the community.